Modified Wiener estimation of diffuse reflectance spectra from RGB values by the synthesis of new colors for tissue measurements - Chen, Shuo (2013)
We present a new method for the accurate estimation of diffuse reflectance spectra from RGB values based on Wiener estimation. In the proposed method, a system matrix obtained from the original RGB values is combined with a set of synthetic optical filters to generate another three values corresponding to new colors. A modified Wiener matrix can then be created with the original RGB values and the new color values, which will yield a more accurate estimation because of the new color information that has been incorporated. This method was tested on in vivo color measurements from 200 skin sites in 10 volunteers. The results show that the proposed method is able to improve the estimation accuracy significantly compared with the traditional Wiener estimation method. The fast speed of this method may enable the estimation of diffuse reflectance spectra at multiple tissue locations from color images in real time, which provides a cost-effective alternative to spectral imaging with the additional advantage of high spectral resolution.